Not ‘just’ climate adaptation—towards progressive urban resilience - Paul O’Hare (Humanities & Social Sciences Communications)
Climate breakdown poses immense—potentially existential— threats to global economies, societies, and ecosystems. Mitigation must be pursued with vigour. However, given the consensus regarding the inevitability of climate change, and the doom-laden predictions of its impacts, adaptation is urgent. Yet progress remains slow, uncoordinated, and fraught with challenges. A particular issue is a lack of clarity—or inconsistency—regarding the framing of adaptation and resilience. In some contexts, interpretations of resilience are criticised for lacking ambition or for being regressive. In others, adaptation is critiqued for reinforcing inequity or for failing to contend with systemic drivers of risks. Such analyses can be deployed to illuminate how resilience and adaptation policy and practice might be catalysed in more sensitive and transformative ways. Learning from disparate evaluations of resilience and adaptation and reflecting on policy development in a large European city, the paper advocates for ‘progressive resilience’. This interpretation aligns resilience (and adaptation) with socially, economically, and politically progressive agendas that are infused with a greater sense of spatial, temporal and social justice. Ultimately, the article articulates reference points for developing climate risk assessments and resilience plans and policies that offer ‘more than just’ adaptation, thereby supporting sustainable and inclusive socio-ecological interventions in an increasingly uncertain and dangerous world.